The Need for Affirming Health Care among LGBTQ+ Survivors of Intimate Partner Violence (Global Journal of Human-Social Science, 2024)
Lesbian gay bisexual trans queer and others who are not heterosexual and cisgender LGBTQ are a growing population in the United States and globally however they are more likely to report health conditions while are simultaneously more likely to struggle attaining patient centered or affirming health care Struggles to receive care are amplified by the lack of formal policy that views health care as a human right This population is also more vulnerable to several risk factors including intimate partner violence IPV than cisgender and heterosexual people Therefore they are more likely to necessitate medical care due to injuries e g broken bones vaginal trauma lost teeth In the absence of macro-level policy protections we make the case for patient-centered and affirming health care that addresses health inequities and the negative health outcomes for IPV survivors We provide recommendations for providers in primary care emergency rooms obstetrics and gynecology and dentistry
Keywords: abuse; bisexual; constitutional rights; domestic violence; fourteenth amendment; gay; lesbian; medicine; sexual minority; transgender